The Effect of Knowledge, Education, Income, and Marriage Age on Iron Deficiency Anemia in Pregnant Women in Taiz City-Yemen - Lamia A. S. Ali; Hermanto Tri Joewono; Widati Fatmaningrum; Riyadh A. S. Thabit; Hebah H. M. Almothana; Fardous G. Alsoufi; Aya Ali Abdullah; Tasnim Mohammed Al-Qadhi; Suha Ali Al Hajj; Samar A. A. Ahmed; Sarah A. D. Alselwi; Habib Thabet; et al. (Amerta Nutrition)
Background: Iron Deficiency Anemia (IDA) is one of the most common types of nutritional anemia in pregnant women and is the most dangerous to the mother and fetus; This is because the need for iron for both the mother and the fetus increases gradually during pregnancy and reaches its highest levels at the end of pregnancy.